2012
DOI: 10.1021/jm300251n
|View full text |Cite
|
Sign up to set email alerts
|

Novel 18F-Labeled Benzoxazole Derivatives as Potential Positron Emission Tomography Probes for Imaging of Cerebral β-Amyloid Plaques in Alzheimer’s Disease

Abstract: Two radiofluoro-pegylated phenylbenzoxazole derivatives, 4-(5-(2-(2-(2-[(18)F]fluoroethoxy)ethoxy)ethoxy)benzo[d]oxazol-2-yl)-N-methylaniline ([(18)F]24) and 4-(5-(2-(2-(2-[(18)F]fluoroethoxy)ethoxy)ethoxy)benzo[d]oxazol-2-yl)-N,N-dimethylaniline ([(18)F]32), were synthesized and evaluated as probes for imaging cerebral β-amyloid (Aβ) plaques in living brain tissue by PET. [(18)F]24 and [(18)F]32 displayed high affinity for Aβ(1-42) aggregates (K(i) = 9.3 and 3.9 nM, respectively). In vitro autoradiography wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 29 publications
2
46
1
Order By: Relevance
“…99m Tc-labeled 2-pyridinylbenzoxazole derivatives [ 99m Tc]18 and [ 99m Tc]20 displayed slightly lower initial brain uptake, but higher brain 2min / brain 60min ratio than 99m Tc-labeled 2-phenylbenzoxazole derivatives [ 99m Tc]17 and [ 99m Tc]19. This observation was in accordance with the 18 F-labeled benzoxazole derivatives reported previously [26,27]. In addition, the N,N-dimethylated derivatives displayed higher initial brain uptake and brain 2min /brain 60min ratio than the N-monomethylated analogs ( 19 with a short propoxy spacer exhibited about two-folder higher initial brain uptake and comparable brain 2min /brain 60min ratio [22].…”
Section: In Vivo Biodistribution In Normal Micesupporting
confidence: 91%
See 1 more Smart Citation
“…99m Tc-labeled 2-pyridinylbenzoxazole derivatives [ 99m Tc]18 and [ 99m Tc]20 displayed slightly lower initial brain uptake, but higher brain 2min / brain 60min ratio than 99m Tc-labeled 2-phenylbenzoxazole derivatives [ 99m Tc]17 and [ 99m Tc]19. This observation was in accordance with the 18 F-labeled benzoxazole derivatives reported previously [26,27]. In addition, the N,N-dimethylated derivatives displayed higher initial brain uptake and brain 2min /brain 60min ratio than the N-monomethylated analogs ( 19 with a short propoxy spacer exhibited about two-folder higher initial brain uptake and comparable brain 2min /brain 60min ratio [22].…”
Section: In Vivo Biodistribution In Normal Micesupporting
confidence: 91%
“…Then, a series of 18 F-labeled benzoxazole derivatives have been reported by our group [26,27]. The results all showed that benzoxazole derivatives have high affinity to Ab aggregates and excellent in vivo brain pharmacokinetics, which confirmed that the benzoxazole scaffold was a promising lead compound for the development of Ab plaque imaging agents.…”
Section: Introductionmentioning
confidence: 89%
“…The O-methyl groups of 24, 25, 36, and 37 were removed by reacting with BBr 3 in CH 2 Cl 2 to give 26, 27, 38, and 39 in yields of 97%, 89%, 88%, and 68%, respectively. Then the hydroxy groups were coupled with 1-bromo-2-fluoroethane to give the fluorinated derivatives (32,33,44, and 45) with one ethoxy unit as the PEG linkage. The corresponding fluorinated derivatives with two or three ethoxy units (28−31 and 40−43) were prepared by the hydroxyl compounds with K 2 CO 3 and the intermediate 20 or 21 in DMF (yield, 40−75%).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The strategy of FPEG was successfully applied to the benzoxazole scaffold, and it has been demonstrated that the fluoro-pegylated phenylbenzoxazole derivatives ([ 18 F]13, [ 18 F]14) showed more promising in vivo kinetics than the corresponding radioiodinated ligand and the benzofuran derivatives. 32 Tracer [ 18 F]13 with a monomethylamino group exhibited high affinity for Aβ aggregates (K i = 9.3 nM) and high initial uptake into the brain and displayed excellent binding to Aβ plaques in ex vivo autoradiographic experiments with Tg2576 mice. What's more, small-animal PET studies demonstrated significant differences between Tg2576 and wild-type mice in the clearance profiles after the administration of [ 18 F]13.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Indeed, it was reported that several Aβ probes with single-digit nanomolar Ki values for the Aβ aggregates successfully stained the Aβ plaques in brain sections of the Tg2576 mice by in vitro autoradiography 25,26 . In addition, it has been shown that chalcone derivatives with a dimethylamino group at the third position can be used to visualize Aβ plaques by in vitro autoradiography 19,27 .…”
Section: In Vitro Autoradiographymentioning
confidence: 99%